2020
DOI: 10.1155/2020/2539482
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Toxoplasma gondii Infection in Patients with Colorectal Cancer in Eastern China: Seroprevalence, Risk Factors, and a Case–Control Study

Abstract: The aim of this study was to explore the epidemiology of Toxoplasma gondii infection in patients with colorectal cancer (CRC) in eastern China. Therefore, 287 primary CRC patients and 287 age-matched healthy control subjects were recruited to estimate the seroprevalence of T. gondii and identify the risk factors of infection. Enzyme-linked immunoassays were used to test for anti-T. gondii immunoglobulin G (IgG) and IgM antibodies. Forty-six (16%) samples were positive for anti-T. gondii IgG antibodies in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…T. gondii achieves persistence in host cells by manipulating many signaling pathways, which are closely related to immune and inflammatory responses ( 34 ), and may cause severe damage to immunodeficient or immunocompromised hosts. Epidemiology in various region surveys has shown that the seroprevalence of T. gondii is significantly increased in both elderly patients and cancer patients ( 35 , 36 ). Moreover, the other genes associated with cg11676291 MORN1 were also enriched in immune-related pathways, including the T-cell receptor signaling pathway, B-cell receptor signaling pathway, Th17 cell differentiation, and Th1 and Th2 cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…T. gondii achieves persistence in host cells by manipulating many signaling pathways, which are closely related to immune and inflammatory responses ( 34 ), and may cause severe damage to immunodeficient or immunocompromised hosts. Epidemiology in various region surveys has shown that the seroprevalence of T. gondii is significantly increased in both elderly patients and cancer patients ( 35 , 36 ). Moreover, the other genes associated with cg11676291 MORN1 were also enriched in immune-related pathways, including the T-cell receptor signaling pathway, B-cell receptor signaling pathway, Th17 cell differentiation, and Th1 and Th2 cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographic data (including age, residence area, and occupation) were collected from participants. Lifestyle variables, including contact with animals (cats, pigs, and/or dogs), consumption of undercooked meat, of raw vegetables or fruits, contact with soil, and source of drinking water, were obtained via a structured questionnaire ( Yu et al, 2020 ). Clinical data were collected from the participant’s medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Serum samples were tested for IgG and IgM antibodies against T. gondii using enzyme-linked immunosorbent assay (ELISA) kits (Kanghua Bio, Beijing, China), as previously described ( Yu et al, 2020 ). Briefly, serum (10 μL) and sample diluent (100 μL) were mixed and dropped into a well on the plate coated with T. gondii antigen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations